2000
DOI: 10.1088/0953-8984/12/10/312
|View full text |Cite
|
Sign up to set email alerts
|

Charge state of paramagnetic E´ centre in thermal SiO2layers on silicon

Abstract: Comparison between the densities of positive charge and paramagnetic E´ centres (O3 Si defects) generated in thermal SiO2 layers on Si by 10 eV photons at different electric field strengths in the oxide demonstrates that the paramagnetic states cannot be associated with positively charged centres, i.e., the E´ centre is neutral. The variation in E´ density results from the balance between activation by irradiation and passivation with radiolytic hydrogen. Therefore, the neutral diamagnetic state of the defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 36 publications
3
40
0
1
Order By: Relevance
“…Note the results of recent experiments [36] that provide an evidence of the involvement of H and positive charge trapping in silicon dangling bond formation in the SiOSiO 2 interface. In this case, apart from Si 3 'SiOH, of course, other structural elements such as Si 2 O'SiOH, SiO 2 'SiOH, and O 3 'SiOH at the interface may be also involved in dissociation process, and they need to be tested separately.…”
Section: Khakimov Et Almentioning
confidence: 65%
“…Note the results of recent experiments [36] that provide an evidence of the involvement of H and positive charge trapping in silicon dangling bond formation in the SiOSiO 2 interface. In this case, apart from Si 3 'SiOH, of course, other structural elements such as Si 2 O'SiOH, SiO 2 'SiOH, and O 3 'SiOH at the interface may be also involved in dissociation process, and they need to be tested separately.…”
Section: Khakimov Et Almentioning
confidence: 65%
“…It was concluded that P b1 does not form electrically active states within the silicon band gap [74]. Concerning the E´center in thermal oxide, it is neutral when paramagnetic and strongly interacts with hydrogen [75]. The model for the E´center in this case is the Hterminated center denoted as O 3 Si-H.…”
Section: à2mentioning
confidence: 99%
“…possible involvement in the charge transport or trapping. At the same time there is plenty of experimental evidence indicating hydrogen as an important factor of charging, for instance of SiO 2 insulating films and their interfaces (Nicollian et al, 1971;Feigl et al, 1981;Gale et al, 1983;Stahlbush et al, 1993;de Nijs et al, 1994;Cartier and Stathis, 1995;Afanas'ev et al, 1995a,b;Afanas'ev and Stesmans, 1998a,b, 1999b, 2000a,b, 2001aVanheusden et al, 1995Vanheusden et al, ,1997Rivera et al, 2002). Therefore, identification of hydrogen-related charge transport and trapping interaction is gaining more importance as novel oxide-based insulators attract increasing attention (see, e.g., Afanas'ev and Stesmans, 2002 for some high-permittivity insulating metal oxides.…”
Section: Monitoring the Injection-induced Liberation Of Hydrogenmentioning
confidence: 99%